2013
DOI: 10.5296/jsr.v4i1.2921
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of Organizational Commitment for Knowledge Sharing Case Study: Shiraz University of Medical Sciences

Abstract: Sustained success in the new organizations depends on the creation, sharing and applying knowledge as an intellectual capital. Among various organizational factors, organizational commitment and its relationship with knowledge sharing had less been considered. This study investigated the relationship between organizational commitment and knowledge sharing from the perspective of Shiraz University of Medical Sciences (SUMS) faculties. Organizational commitment includes affective, normative and continuous commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
(13 reference statements)
3
10
0
3
Order By: Relevance
“…Other studies discussed the relationship between human resource management and organizational commitment (see for example Edgar & Geare, 2005;Sanders et al, 2008;Juhdi et al, 2011;Zaitouni et al, 2011;Imran & Ahmed, 2012). Whereas, (Malhotra & Galletta, 2003;Alvesson, 2005;Thompson & Heron, 2005;Rocha et al, 2008;Chiang et al, 2011;Neyestani et al, 2013) investigated the relationship between organizational commitment and knowledge management process. This section discussed the previous literature related to the subject of this study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other studies discussed the relationship between human resource management and organizational commitment (see for example Edgar & Geare, 2005;Sanders et al, 2008;Juhdi et al, 2011;Zaitouni et al, 2011;Imran & Ahmed, 2012). Whereas, (Malhotra & Galletta, 2003;Alvesson, 2005;Thompson & Heron, 2005;Rocha et al, 2008;Chiang et al, 2011;Neyestani et al, 2013) investigated the relationship between organizational commitment and knowledge management process. This section discussed the previous literature related to the subject of this study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Menurut Bock & Kim (2002), bahwa orang-orang yang memiliki efikasi diri tinggi akan lebih memiliki power dan keyakinan diri berbagi pengetahuan yang bernilai dan bergurna kepada orang lain. Menurut Yousefi (2010) dalam Neyestani, Piran, Nasabi, Nosrati, & Maidanipour (2013), bahwa karyawan yang komit terhadap organisasinya akan lebih kooperatif dan aktif dalam berbagi pengetahuan. Dengan demikian dapat dikatakan bahwa aktivitas berbagi pengetahuan karyawan Kantor Cabang Utama PT Bank Panin Tbk Kota Pontianak dapat dipengaruhi oleh faktor efikasi dan komitmen organisasional karyawan.…”
Section: Pendahuluanunclassified
“…Explicit knowledge adalah pengetahuan yang bersifat formal, tertulis dan sistematis yang mudah untuk dikomunikasikan dan dibagikan di antara individu dalam organisasi. Nonaka (1995) (Neyestani et al, 2013).…”
Section: Kajian Literaturunclassified
See 1 more Smart Citation
“…This study may also provide an implication to the government on how to reduce domestic economic gaps between regions to attain sustainable development because previous study showed that greater equality of income increased the duration of countries' economic growth spells more than free trade, low government corruption, foreign investment, or low foreign debt (Berg & Ostry, 2011). Accordingly, it may not be unreasonable to assume that if Vietnamese laborers in corporations in backward regions could have higher OC, the economies would show higher performances by retaining high-quality employees in particular workplaces for a long period, which enables smoother technological transfer, knowledge sharing and organizational growth in a corporation (Chiang, Han, & Chuang, 2011;Neyestani, Piran, Nasabi, Nosrati, & Maidanipour, 2013), and accordingly would promote balanced and long-standing national development.…”
Section: Introductionmentioning
confidence: 99%